3D modelling of the upper Tortonian-lower Messinian shallow ramp carbonates of the Hyblean domain (Central Mediterranean, Faro Santa Croce, Sicily). (January 2022) - Tomassetti, Laura; Brandano, Marco; Mateu-Vicens, Guillem
Abstract: This work illustrates a combined modelling approach using digital photogrammetry and geological modelling to create a high detailed 3D facies model of the inner environment of the Monte Carrubba carbonate ramp outcropping in the South Sicily. The Monte Carrubba Formation (Tortonian-lower Messinian) is the youngest marine Miocene carbonate deposit of the Hyblean region, prior to the Messinian crisis of the Mediterranean. In particular, Faro Santa Croce outcrop, which is in vertical thickness up to 8 m, shows the most proximal sector of this ramp. The Faro Santa Croce outcrop offers the opportunity to investigate and reproduce a highly-detailed facies heterogeneity 3D model for a very narrow and limited area of few squared kilometers (0.1 Km 2 ), developed in a tectonically stable area. Within this small areal, five facies have been recognized and modelled revealing a high level of facies heterogeneity. In this area marine ooidal shoals (ooidal grainstone to packstone) interfingered with shallow water seagrass environment (green-algal-floatstone facies and bioclastic grainstone-to-packstone facies) with abundant mollusc fauna. The distal part of this vegetated environment (fine-grained mollusc-packstone facies) passed basinward into coral mounds (coral boundstone). The combination of digital photogrammetry and 3D geological modelling software has allowed to obtain a very high-resolution model of facies heterogeneity, evidencing the complexity of facies associations and, in particular, the development of a facies mosaic that can be underestimated by a classical 1D or 2D field analysis, especially in limitedly exposed outcrops. Highlights: Outcrop, digital outcrop model through photogrammetry and 3D geological modelling interpretation. Realization of high detailed 3D facies model of an inner environment of an Upper Miocene carbonate ramp. Combination of digital photogrammetry and 3D geological modelling as means to obtain a high-resolution model of facies heterogeneity within a facies mosaic arrangement.